Development Integration of Ability to Master Turats and Arabic Language Skills - Mohammad Makinuddin; Friendis Syani Amrulloh (Kilmatuna: Journal Of Arabic Education, 2025)
Pesantren is an Islamic educational institution that plays an important role in maintaining the Islamic scientific tradition through learning Turats and Arabic. However, in its development, the mastery of Turats among santri experiences various challenges, such as low interest in learning, monotonous teaching methods, and limited learning resources. Arabic language as the main key in understanding Turats is also often not optimally mastered by santri. Therefore, this study aims to analyses the relationship between mastery of Turats and Arabic language skills in pesantren, as well as to develop an innovative and interactive learning integration model to improve santri understanding. This research uses a descriptive method with a literature review approach. Data were collected from various academic literatures, such as journals, books, and scientific publications that discuss Turats learning methods and Arabic teaching strategies. The data obtained were then analyzed using thematic synthesis techniques to identify the main patterns in the integration of Turats and Arabic learning. The results show that the integration of Turats and Arabic learning in pesantren is an effective strategy in improving santri's understanding of Islamic literature while strengthening their Arabic language skills. Traditional methods such as sorogan and bandongan are proven to help santri deepen their understanding of classical Islamic texts and enrich their Arabic vocabulary and grammar. In addition, the curriculum approach that combines school, tutorial and dormitory learning further optimises learning effectiveness. Despite the challenges in teaching creativity and innovation, this integration remains a key strategy in ensuring santri have a strong religious understanding as well as Arabic language skills for the global era.